Technology Entrepreneurship: Ingenious.Ly Sdn. Bhd. / Nur Liana Mohd Rashid… [et al.] - Mohd Rashid, Nur Liana; Faizul Azran, Nur Azreen; Afizan, Ainin Sorfina; Binyamin, Nur Ainaa Tasnim (2020)
Honey sleek pump is built to help the small-scale bee farmers in Malaysia. There are few main features that is highlighted for this product which is not vacuum based where there are no leaking problems that make slow suction. Therefore, there will be no bottle explosion problems. Besides, the honey sleek pump is invented to be pump directly honey and not air. This specification will reduce honey bubbling problems for a better storage. The honey sleek pump is using the super compact battery with 6800mAH capacity. This feature meet the demands of customers who want tools that are easy to carry everywhere. Furthermore, this product is using 12W energy saving motor. The advantage is that it could sustain the battery for 6-7 hours per charging. Next, the product is set on the modest speed. This speed mode is expected to harvest 1kg honey for about 15 to 20 minutes only.